Simultaneous determination of bioactive marker compounds from Gardeniae fructus by high performance liquid chromatography - Lee, Eun Ju; Hong, Jun Kee; Whang, Wan Kyunn (Archives of pharmacal research, 2014)
Gardeniae fructus is one of the medicinal herbs that have been used in Far Eastern countries, such as Korea, China, and Japan. Gardeniae fructus is the dried ripe fruit of Gardenia jasminoides Ellis (Rubiaceae) and has been used as a yellow dye. It is widely used as traditional herbal medicine for reducing fever, cholagogue, diuretic and antiphlogistic effects. We established an analytical method that was useful to evaluate the quality control, and standardize quantification monitoring of 68 samples of Gardeniae fructus collected from Korea and China. While numerous previous studies have focused on the simultaneous analysis of geniposide, which constitutes the higher proportion of Gardeniae fructus, and crocin, which determines its color, no simultaneous analysis of gardenoside and geniposide, the major components of Gardeniae Fructus, has been performed. However, previously reported methods are not considered accurate enough because only geniposide or gardenoside was chosen to be the marker component for the quality control of Gardeniae fructus. Thus, we developed the method using simultaneous determination of four components including geniposide, gardenoside, geniposic acid and chlorogenic acid. Against this backdrop, this study aims to propose a new calculation for gardenoside and geniposide concentrations by analyzing their concentrations in Gardeniae fructus.